Dual exchange membrane fuel cell with sequentially aligned cation and anion exchange membranes for non-humidified operation - Lee, So Young; Chae, Ji Eon; Choi, Jieun; Park, Hyun Seo; Henkensmeier, Dirk; Yoo, Sung Jong; Kim, Jin Young; Na, Youngseung; Jang, Jong Hyun; Kim, Hyoung-Juhn (ELSEVIER, 2020)
To realize effective polymer electrolyte fuel cell (PEFC) operation under non-humidified conditions, a new self-humidifying dual exchange membrane fuel cell (DEMFC) was designed and evaluated. The DEMFC was fabricated using sequentially aligned membrane electrode assemblies (MEAs) consisting of an anion exchange membrane (AEM) and a cation exchange membrane (CEM). In this system, water simultaneously generated by the half-cell reactions at both the anode and the cathode is then supplied to the other MEA through the gas diffusion medium and the bipolar plate in the DEMFC under completely dry conditions, resulting in high cell performance. Also, durability of a DEMFC five-cell stack was tested by accelerated on/off operation under fully dry conditions. No cell degradation occurred over 50 cycles (200 h), indicating that this DEMFC design provides an effective approach for constructing practical miniaturized PEFCs that do not require external humidification systems.